Mandating Corporate Sustainability: Legal Frameworks for ESG Compliance and Green Financing in Indonesian State-Owned Enterprises (SOEs) - Debi Masri; Muammar Rinaldi; Tina Muhardika Handayani (Outline Publisher, 2026)
This study aims to examine the mechanisms through which the stringency of the ESG legal framework influences the financial performance of Indonesian state-owned enterprises (SOEs), via the mediating role of green financing adoption and ESG performance, and the moderating roles of sustainability management control systems and regulatory enforcement effectiveness. A quantitative associative design was employed, collecting perceptual data from 47 middle-to-senior managers across 16 SOEs operating in Medan, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test a moderated mediation model. The results reveal that perceived legal stringency positively drives green financing adoption, which in turn enhances financial performance indirectly through improved ESG outcomes, indicating full mediation. Furthermore, the translation of green financing into ESG improvements is significantly strengthened when sustainability management control systems are robust. The positive impact of legal stringency on financial performance is also amplified by the perceived effectiveness of regulatory enforcement.